Fonógrafos e Gramofones : mediações técnicas em Porto Alegre (1892 – 1927) - Cascaes, Julio César Silveira (2016)
This paper discusses the history of mechanical sound recording devices and their subscription to the musical production chain and their development in Brazil, having printed sources, especially newspapers and magazines, as the means for analysis. Phonographs contributed for several technological innovations in the field of communication, but were also effective for the register of musical pieces. In the 20th century, Gramophones and records quickened the processes of mediation between the instances of production and the audiences, strengthening the first phonographic companies. The first phonograph arrived in Brazil in 1878 as a great technological innovation. The starting point is the premise that the press took fundamental part in the consolidation of these devices in the country. We intend to place sound reproducing devices within the context of representations of modernity, starting from the study of the urban changes taking place in Rio de Janeiro, São Paulo and Porto Alegre. The social environments of musical exchanges, the roles of cultural mediators and the main agents of technological interchange are examined in order to verify their contributions for the first phonographic records. Finally, the printed sources from Porto Alegre are analyzed so the emergence of phonographs and Gramophones can be featured. Taking urban growth, musical culture and the first phonographic experiences into account, this study will assemble city historians, old chroniclers, press critique, pieces of advertisement, catalogs and all sorts of printed material relevant to the mapping of the presence of phonographs and Gramophones in streets, bars and business establishments, probing, through texts and discourses, the exaltation of, the indifference towards and the reactions against the mechanical technology of sound recording.